A Critical Discourse Analysis of News Report on Kanjuruhan Tragedy in Tempo and CNN Indonesia - Dewi Ikke Nuryani; Bambang Wibisono (ELITE JOURNAL, 2023)
Critical Discourse Analysis aims to explore the hidden ideology of the discourse, thereby exposing injustice, discrimination and prejudice in the discourse. The Kanjuruhan tragedy occurred in October 1st 2022, which caused hundreds of football supporters and two police officers died. It is due to many supporters were stepped on and run out of oxygen. This article uses Fairclough three-dimensional framework and Hallyday’s systemic functional grammar as tools, and select the news about the chronology of the Kanjuruhan tragedy based on two different news media Tempo and CNN Indonesia. After analysis, it is found that Tempo tends to blame police institution towards Kanjuruhan tragedy but CNN Indonesia tends to blame the supporters. Keywords: Critical Discourse Analysis, three-dimensional Fairclough, Kanjuruhan.